2012
DOI: 10.3174/ajnr.a3127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cilostazol in Preventing Restenosis after Carotid Artery Stenting Using the Carotid Wallstent: A Multicenter Retrospective Study

Abstract: BACKGROUND AND PURPOSE:Restenosis after CAS is a postoperative problem, with a reported frequency of approximately 2%-8%. However differences in stent design, procedure, and the antiplatelet agent appear to affect the incidence of restenosis. We assessed the frequency of restenosis and the effect of the antiplatelet agent CLZ in preventing restenosis after CAS by the standard procedure using the CWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Regarding major/minor bleeding, 3 of the studies 17,20,21 did not report any result and 2 studies 16,22 reported null bleeding events after CAS. Only one study 19 reported 7 bleedings overall (6 access site hematomas and 1 hemorrhage due to Regarding the revascularization rate post ISR, only 3 studies 18,19,22 reported a pooled rate of 33 endovascular treatments in 51 cases of ISR (65%) without stratifying the results according to antiplatelet treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding major/minor bleeding, 3 of the studies 17,20,21 did not report any result and 2 studies 16,22 reported null bleeding events after CAS. Only one study 19 reported 7 bleedings overall (6 access site hematomas and 1 hemorrhage due to Regarding the revascularization rate post ISR, only 3 studies 18,19,22 reported a pooled rate of 33 endovascular treatments in 51 cases of ISR (65%) without stratifying the results according to antiplatelet treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding clinical events post CAS, data were adequate for comparison in only 5 trials 16,17,19,21,22 for 30-day outcomes and in 4 trials [17][18][19]21 for outcomes during the followup period. As no heterogeneity was identified, fixed-effect models were utilized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations